Strategi Pengembangan Berkelanjutan Objek Wisata Curug Ciparay di Desa Ciasihan Kecamatan Pamijahan Kabupaten Bogor - Susilawati, Yeti; Fadiarman (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
The issue is that Curug Ciparay tourism attractions have not been fully developed, which results in a low volume of visitors. In Ciasihan Village, Pamijahan District, Bogor Regency, the Curug Ciparay is a popular tourist destination. The goal of this study is to examine its sustainable development approach. This research is crucial for developing pertinent strategic or legislative solutions for the expansion of sustainable tourism. This study employs multiple data collection methods, including observation, interviews, and documentation, as well as descriptive methods. To verify and evaluate the field data that has been gathered, a SWOT analysis was performed. The study's findings suggest that the tourist destination of Curug Ciparay, with all of its amenities, is a well-kept secret. Empirically, this waterfall is encouraging and, if it is developed by connected parties in the best way, it will have a big influence. For the management of Curug Ciparay tourism, alternative development approaches can be suggested, such as enhancing and maintaining regional facilities and infrastructure, maximizing the inherent potential and distinctiveness of tourist attractions to compete with other destinations, utilizing human resources and a skilled workforce, and cooperating with related parties. The associated parties in question include government agencies with the authority to regulate Indonesian tourism, as well as universities, financiers, and tour operators. They also include social media promotion.